Advancements in Carbazole-Based Sensitizers and Hole-Transport Materials for Enhanced Photovoltaic Performance - Ayagoz Ibrayeva; Urker Abibulla; Zulfiya Imanbekova; Bakhytzhan Baptayev; Robert J. O’Reilly; Mannix P. Balanay (Molecules)
Carbazole-based molecules play a significant role in dye-sensitized solar cells (DSSCs) due to their advantageous properties. Carbazole derivatives are known for their thermal stability, high hole-transport capability, electron-rich (p-type) characteristics, elevated photoconductivity, excellent chemical stability, and commercial availability. This review focuses on DSSCs, including their structures, working principles, device characterization, and the photovoltaic performance of carbazole-based derivatives. Specifically, it covers compounds such as 2,7-carbazole and indolo[3,2-b]carbazole, which are combined with various acceptors like benzothiadiazole, thiazolothiazole, diketopyrrolopyrrole, and quinoxaline, as reported over the past decade. The review will also outline the relationship between molecular structure and power-conversion efficiencies. Its goal is to summarize recent research and advancements in carbazole-based dyes featuring a D-π-A architecture for DSSCs. Additionally, this review addresses the evolution of carbazole-based hole-transport materials (HTMs), which present a promising alternative to the costly spiro-OMeTAD. We explore the development of novel HTMs that leverage the unique properties of carbazole derivatives to enhance charge transport, stability, and overall device performance. By examining recent innovations and emerging trends in carbazole-based HTMs, we provide insights into their potential to reduce costs and improve the efficiency of DSSCs.